U.S. peacefare organizing American peace-building operations - Smith, Dane F. (ABC-CLIO,LLC, 2010)
After a review of the historical roots of American peacefare, the study examines five key bureaucratic entities involved in peace-building. The analysis is Washington-centered, focused on organization and the interagency process, and gives relatively little space to overseas implementation. It is based largely on more than 120 interviews with current and previous government officials. The study begins with the National Security Council (NSC), covering the Cabinet-level officials meeting with the President as a council, as well as the NSC staff, which serves as the foreign policy/national security staff of the President. It goes on to consider the role of the State Department, exercised both through the diplomacy of its geographic bureaus and the specialized programs of certain functional bureaus. A separate chapter is devoted to the State Department's new formal mechanism for coordination, the Office of the Coordinator for Reconstruction and Stabilization. The following chapter outlines the zigzag route followed by the Defense Department under the Clinton and George W. Bush administrations in dealing with stability operations.USAID's increased attention to shaping foreign assistance and development to the dynamics of conflict is then chronicled. The survey of agencies ends with the unique and evolving role of the U.S. Institute of Peace, a nonpartisan body formally independent of the executive branch. The budget process for U.S. peacefare is traced through Function 150 (international affairs) and more cursorily through Function 050 (defense) to the actions ofauthorizing and appropriating committees in the Congress. The book ends with recommendations to the Obama administration for strengthening U.S. peacefare, drawing from the experience of the past two decades